Optimization of Human Resources and Machines to Fulfill Customer Orders at PT XYZ - Hasan As’ari; Tukhas Shilul Imaroh (Cita konsultindo, 2024)
This study explores the challenges faced by the plastic manufacturing company PT XYZ, which produces make-to-order masterbatch. The primary issue is the untimely distribution schedule, which results in an inability to meet production targets. The unknown production capacity leads to bottlenecks in the production process. The study employs the Rough Cut Capacity Planning (RCCP) method to calculate the production capacity of each work station. The analysis results reveal that work stations SK1, SK2, SK3, SK4, and SK5 experience bottlenecks due to capacity demands exceeding available capacity. Suggested solutions include increasing working hours for SK1 (36 hours), SK2 (19 hours), SK3 (5 hours), SK4 (111 hours), and SK5 (45 hours) to address these bottlenecks. Further optimization using Linear Programming POM-QM shows that the RCCP method has achieved optimal results, with the company required to produce 12.95 units of product A, 7.27 units of product B, 4.12 units of product C, and 3.75 units of product D. The combination of RCCP and Linear Programming methods enables the company to efficiently determine the required capacity, address bottlenecks, and ensure optimal fulfillment of customer orders.